The Credit Boom in the EU New Member States : Bad Luck or Bad Policies? (IMF Working Papers; Working Paper ;, 2010)
In the past decade, most of the EU New Member States experienced a severe credit-boom bust cycle. This paper argues that the credit boom-bust cycle was to a large extent the result of factors external to the region ('bad luck'). Rapid credit growth followed from a high liquidity in global markets and the particular attractiveness of 'new Europe' for capital flows, while the end of the credit cycle was brought about by a global crisis. However, the fact that some countries managed to avoid most of the excesses, including asset price bubbles and foreign exchange lending, suggests that policies and policy failures ('bad policies')-in particular overly expansionary macroeconomic settings and excessively optimistic views on prudential risks-also have played a critical role.